Peningkatan Kosa Kota Bahasa Arab Siswa Dengan Metode Cooperative Learning Di Mi Ma’arif Tempuran - Furoidah, Asni; Mufidah, Auliya Elmi (An-Nuqthah, 2024)
In the application of cooperative learning in the MI environment, students lack understanding of the subject matter given by the teacher even though it is only a few vocabulary, but with the lack of students in collaborating and being active in these activities, it is undeniable that students still have confidence in their abilities. This service aims to describe cooperative learning, a learning model that is expected to be one of the successful solutions in learning Arabic. In this service research, the researcher uses the community service method. The researcher also collects data through observation and documentation based on primary and secondary sources. The results of this research show that the cooperative learning method can make it easier for teachers to find out students who do not understand Arabic vocabulary. Thus, it can be concluded that the application of Arabic language learning using the cooperative learning method of team games tournaments (TGT) can improve students' Arabic vocabulary at MI Ma'arif Tempuran